2005
DOI: 10.1093/nar/gki655
|View full text |Cite
|
Sign up to set email alerts
|

Excision of formamidopyrimidine lesions by endonucleases III and VIII is not a major DNA repair pathway in Escherichia coli

Abstract: Proper maintenance of the genome is of great importance. Consequently, damaged nucleotides are repaired through redundant pathways. We considered whether the genome is protected from formamidopyrimidine nucleosides (Fapy•dA, Fapy•dG) via a pathway distinct from the Escherichia coli guanine oxidation system. The formamidopyrimidines are produced in significant quantities in DNA as a result of oxidative stress and are efficiently excised by formamidopyrimidine DNA glycosylase. Previous reports suggest that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Endo III was found to moderately discriminate the bases placed opposite to the lesion; the order of preference G Ͼ A Ͼ T Ͼ C was observed. This order is in agreement with the data obtained for other lesions showing at most a severalfold preference for G over A and purines over pyrimidines (48,51,52). No significant difference was observed when the reaction products were treated or not by alkali, indicating that the AP lyase activity does not limit the reaction and proceeds with a rate similar to the rate of the glycosylase reaction; this is consistent with the observation of only a single fluorescence change in both AP substrate and dHU substrate cleavage.…”
Section: F/tcsupporting
confidence: 92%
See 1 more Smart Citation
“…Endo III was found to moderately discriminate the bases placed opposite to the lesion; the order of preference G Ͼ A Ͼ T Ͼ C was observed. This order is in agreement with the data obtained for other lesions showing at most a severalfold preference for G over A and purines over pyrimidines (48,51,52). No significant difference was observed when the reaction products were treated or not by alkali, indicating that the AP lyase activity does not limit the reaction and proceeds with a rate similar to the rate of the glycosylase reaction; this is consistent with the observation of only a single fluorescence change in both AP substrate and dHU substrate cleavage.…”
Section: F/tcsupporting
confidence: 92%
“…Opposite Base Specificity of Endo III-It has been reported that the base opposite the lesion may influence the activity of Endo III but the opposite base specificity strongly depends on the lesion: whereas thymine glycol-, 5,6-dihydrothymine-, formamidopyrimidine-, and N-(2-deoxy-␤-D-erythro-pentofuranosyl)-N-3-[(2R)-hydroxyisobutyric acid]-urea-containing substrates show a moderate to pronounced preference for G opposite the lesion, urea, and 5-hydroxycytosine are excised equally well from all pairs (48,51,52). We have examined the opposite base specificity of dHU excision by Endo III in a single turnover mode (Fig.…”
Section: F/tcmentioning
confidence: 98%
“…In a minor role, NTH1 can also participate in FapyG repair, especially if opposite G (not shown), a base composition that could be formed by the misincorporation of Gs opposite FapyG during DNA replication occurs. Equivalently, purified E. coli endonuclease III removed both FapyA and FapyG from DNA, although FapyA was excised more rapidly (37). The small contribution of NTH1 to FapyG repair was also confirmed by the presence of a sodium borohydride-trapped DNA-enzyme complex in extracts from OGG1 Ϫ/Ϫ liver mitochondria not seen in extracts from (OGG1/NTH1) Ϫ/Ϫ animals and by the elevated levels of FapyG in liver genomic DNA from NTH1…”
Section: Discussionmentioning
confidence: 85%
“…Further, oxiway which in mycobacteria includes two homologues each of the structurally related formamidopyrimidine DNA N-glycosylases (Fpg/MutM) and endonuclease VIII (Nei) that have maintained the necessary domains for Fpg and Nei protein function with the exception of fpg2 in M. tuberculosis which lacks the N-terminal domain important for DNA binding and glycosylase activity [9][10][11]. The functional redundancy/substrate overlap displayed by the Fpg/Nei family suggests an efficient mechanism of genome maintenance in mycobacteria [12][13][14][15][16]. In addition, M. tuberculosis retains a single homologue of Endonuclease III (Nth), which belongs to the Nth superfamily of DNA glycosylases [9,17].…”
Section: Introductionmentioning
confidence: 99%